Perilaku Hidup Bersih dan Sehat (PHBS) Tatanan Rumah Tangga Dengan Kejadian Diare pada Balita - Dismo Katiandagho; Anselmus Kabuhung; Agnes T. Watung; Rismon S.Duka; Mokoginta Jusran; Agus Rokot; Sabrina P. M. Pinontoa (Poltekkes Kemenkes Padang, 2022)
Risk factors that increase the incidence of diarrhea are malnutrition, low birth weight, not getting adequate breast milk, crowded living quarters, incomplete immunization. The purpose of this study was to analyze the effect of clean and healthy living behavior in household settings on the incidence of diarrhea in toddlers. This type of research is an analytic observational study with a cross sectional. The sample size in this study were 38 people and 19 samples of dug well water. Research data were analyzed using the chi square. The results of the study proved that there was an influence between the unavailability of family latrines, p = 0.004, PR = 11, 000 there was an influence between the unavailability of clean water facilities, p = 0.035, PR = 6.111, there was an influence between the distance of latrines and SAB that did not meet requirements, value, p = 0.004, PR = 11.000 and there is an influence between the bacteriological quality of clean water that does not meet the requirements and the incidence of diarrhea in toddlers, p = 0.009. Suggestion, for officers of the Minahasa District Health Office and the Papakelan Health Center, to conduct outreach to the community about the importance of providing environmental health facilities in an effort to improve clean and healthy living behavior in household settings to reduce the incidence of diarrhea in toddlers.